KELAYAKAN USAHA PENANGKAPAN IKAN MENGGUNAKAN JARING INSANG (GILL NET) DI WADUK JATIGEDE KABUPATEN SUMEDANG - Wahyu Setiawan; Atikah Nurhayati; Titin Herawati; Asep Agus Handaka (PAPALELE: Jurnal Penelitian Sosial Ekonomi Perikanan dan Kelautan, 2018)
Gill net is one of the fishing gear used by Jatigede Reservoir fisherman. The purpose of this research is to analyzed the feasibility of fish catching business with gill net in Jatigede Reservoir. This research was conducted by used data collection method (observation, questioner, literature study) and method of data analysis (feasibility business analysis). The benefits of this research is expected to be informations and references for the research who will expand a fishing business with gill net at Jatigede Reservoir. The result of feasibility of fish catching business with gill net at Jatigede Reservoir is profit value Rp. 70.890.000, Break Event Point price and production (all species of fish) Rp. 4.154/kg and 2.136kg in a year, Benefit Cost Ratio 3,37, Payback Period 2 months and Net Present Value >1 Rp. 52.820.243, the fish catching business using gill net at Jatigede Reservoir is feasible to be developed.